PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA JARING-JARING BANGUN RUANG - Muhammad Arfan Fadiah; Ratih Purnamasari; Mira Mirawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The influence of the problem- based learning model on the results of learningmathematics nets build space. Thesis of Elementary School Teacher EducationStudy Program, Faculty of Teacher Training and Education, Pakuan University2024. This research is a quasi-experimental study. This study aims to determinethe differences in mathematics learning outcomes of space building nets throughthe Problem Based Learning model. This research was conducted at CipayungState Elementary School 04 Depok City Class V A, and VB in November oddsemester. The calculation of N-Gain Model Problem Based Learning is 79 withhigh criteria, and the N-Gain value of conventional models is 73 with high criteria.So that the N-Gain in the experimental class with the Problem Based Learningmodel is greater than the conventional model control class. Researchers alsoconducted a normality test with a liliefors test of both normally distributed samplesbecause the values of both samples were smaller than Ltabel. In the ProblemBased Learning class group, the Lcalculate ≤ Ltabel value was 0.03 ≤ 0.177, in thecontrol class group, the Lcalculate ≤ Ltabel value was 0.046 ≤ 0.177. Then in thehomogeneity test the data is homogeneous because it is smaller than X2 table,obtained values of 1.12 ≤ 1.98. Furthermore, in the hypothesis test, a tcount of7.89 was greater than the ttable of 2.01063, indicating that H0 (null hypothesis)was rejected and Ha (alternative hypothesis) was accepted. Based on the resultsof the research above, it can be stated that the Problem Based Learning modelhas differences in the results of learning mathematics building space nets, in otherwords that the Problem Based Learning model is more effective than conventionalmodels in learning mathematics building space nets.